2013
DOI: 10.1590/1414-431x20132830
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated blood pressure response during the exercise treadmill test as a risk factor for hypertension

Abstract: Exaggerated blood pressure response (EBPR) during the exercise treadmill test (ETT) has been considered to be a risk factor for hypertension. The relationship of polymorphisms of the renin-angiotensin system gene with hypertension has not been established. Our objective was to evaluate whether EBPR during exercise is a clinical marker for hypertension. The study concerned a historical cohort of normotensive individuals. The exposed individuals were those who presented EBPR. At the end of the observation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
9
1
2
Order By: Relevance
“…For instance, no association was found between exaggerated BP response during treadmill tests and the development of hypertension in 3.5 years of follow-up. 13 Another study showed that the apparent relation between exercise SBP response and left ventricular mass is confounded by age, resting SBP, and body mass, questioning the relevance of positive echocardiographic findings reported in other studies. 14 In a 12-year follow-up of young Japanese adults, exaggerated SBP response during exercise was not associated with hypertension among women.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, no association was found between exaggerated BP response during treadmill tests and the development of hypertension in 3.5 years of follow-up. 13 Another study showed that the apparent relation between exercise SBP response and left ventricular mass is confounded by age, resting SBP, and body mass, questioning the relevance of positive echocardiographic findings reported in other studies. 14 In a 12-year follow-up of young Japanese adults, exaggerated SBP response during exercise was not associated with hypertension among women.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the great range of observation periods used by different studies has significantly influenced their various results. 13 Another concern was the doubts raised regarding the accuracy of BP measurements during exercise and the reproducibility of these results. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, the clinical role of exercise BP is still under evaluation, as there have been some conflicting results among various studies regarding the existence and magnitude of its association with future hypertension. [19][20][21] The field of BP variability has gained increased attention in recent decades, following a few large-scale studies linking long-term variability with higher probabilities for CVD and mortality. 2 Findings from a survey of the general US adult population comprising 956 individuals revealed that higher visit-to-visit variability in resting systolic but not diastolic BP predicted a greater risk for all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In general, research has shown that EBPR to exercise testing in people with no history of high blood pressure can increase the risk of blood pressure by 2 to 3 times ( 8 11 ). Some studies have also reported associations between EBPR to exercise testing and mortality as well as cardiovascular problems, albeit generally with no described mechanism ( 12 ).…”
Section: Discussionmentioning
confidence: 99%